Comportamento de consumo: uma análise dos fatores que controlam a escolha de bebidas, com base no modelo na perspectiva comportamental, de Foxall - Rosenthal, Benjamin (2007)
Consumer behavior is a key issue in modern society and one of the pillars of occidental economies. This research investigated consumer behavior for beverages (beer, soda and juice) through the analysis of one year choices for 423 consumers in the city of Sao Paulo. Such choices were analyzed according to a model (the Behavioral Perspective Model) developed by Gordon Foxall. This model split the benefits (reinforcements) of the brands in both utilitarian and informative and it was created based on Behavior Analysis interpretation of behavior. This study aimed to understand how these benefits (utilitarian and informative) control consumer choices, identifying the levels of loyalty and fidelity of consumers to these benefits. The findings confirm some patterns previously discovered in past studies: a) there was considerable loyalty towards high informative benefits; b) there was considerable loyalty towards low utilitarian benefits; c) loyalty towards specific utilitarian and informative levels were slightly superior to the one s previously identified in other similar studies; d) price did not appeared as a relevant factor in determining brand volume of each main category brand